Effect of Ultra-high Pressure Treatment on the Chemical Properties, Colour and Sensory Quality of Young Red Wine - Sun, X.; Chen, X.; Li, L.; Ma, T.; Zhao, F.; Huang, W.; Zhan, J. (South African Journal of Enology and Viticulture, 2016)
The effects of ultra-high pressure (UHP) treatment on the chemical properties, colour and sensory quality of young red wine were studied. UHP did not significantly affect the alcohol content, and the methanol content was higher than that of the control, with the latter first increasing and then decreasing with the increase in the pressure or period of treatment. The glycerol content was also markedly changed by UHP, although without a regular pattern. The pH value was not markedly changed by the treatments, and the contents of total acids and volatile acids were scarcely affected. The fructose and glucose contents were clearly changed according to the different treatment conditions. The tartaric acid, citric acid and lactic acid levels showed evident changes, whereas the malic acid level was not changed by UHP treatment. The trend of these changes was similar to what occurs during natural ageing. As the pressure of the treatment was increased to 200 MPa, the chroma value increased, followed by a decline upon higher pressure treatments. The hue of the wine was significantly changed by treatment at different pressures, reaching the highest value after treatment at 400 MPa and then decreasing with increasing pressure. The chroma and hue values of the wine were changed significantly according to the duration of the UHP. After UHP, the appearance, aroma and taste of the wine was improved, with the score for appearance obviously increased. When the wine was treated at 500 MPa for 30 min, its sensory quality received the highest score.